Qualidade, perfil eletroforético e de voláteis, fitoquímicos bioativos e atividade antioxidante de frutos de genótipos de macaibeira (acrocomia intumescens drude) - Souza, Cassiara Camelo Eloi de (2016)
The objective of this research was to evaluate the fruit quality of seven native genotypes macaw Atlantic Forest and environment, through physical, chemical, antioxidant capacity, fatty acid profile (GC-FID), Phenolic (HPLC-UV) and volatile (SPME-GC-MS) in order to obtain data on potential use and variability of this species. The pulp and almond can be considered as an important source of carbohydrates, lipids, minerals and K, Fe, Ca and P. Almonds are rich in globulin and do not have trypsin inhibitors and/or haemagglutinating activity. The pulp showed high levels of UFA (89.81%) being more abundant oleic acid (8.09 g.100g-1), linoleic (1.56 g.100g-1) and palmitic acid as well as excellent nutritional quality index. Almond also rich in oleic acid (7.61 g.100g-1) contains significant levels of AGS (14.35 g.100g-1), especially lauric, myristic and palmitic acid. The oils have good thermal stability up to 230 °C with DTA curves of exothermic character. The pulp has very high levels of carotenoids (8.64 mg.100g-1) and can be considered rich in vitamin C (47,60 mg.100g-1). The highest concentrations of total phenolics were observed in the peel (274.55 mg.100g-1) and almond (147.23 mg.100g-1). The strongest positive and significant correlation occurred between ABTS● + and PET. Phenolic acids and flavonols were the main components in the studied fractions. The phenolic catechin was only found in all samples. However, the phenolic myricetin was identified with the highest concentration. Genotype 6 stood out to contain the highest concentrations of carotenoids, yellow flavonoids and PET in the peel, ascorbic acid and yellow flavonoids in the pulp and antioxidant activity in the peel. Genotype 7 has the highest content of carotenoids and PET in the pulp. Through the HS-SPME-GC-MS system was first identified (62) Volatile compounds in the pulp. Terpenes, aldehydes and alcohols were the main. The alcohol content ranged from 1.5 to 44.99%; the dioxalanes were present in all genotypes; the hexanal was the main representative of the aldehydes. The pulp macaw has a strong and exotic aroma and high levels of β-Cis-Ocimene, β-Trans-Ocimene and Allo-aromadendrene. The PCA was efficient to indicate the most significant features in the differentiation between the genotypes that showed genetic variability. This fruit can therefore contribute substantially to the supply of nutrients, dietary enrichment of bioactive source and adding value to natural resources in the Brazilian Atlantic Forest for its fresh or processed consumption.